EFFECTIVENESS OF MARKETING COMMUNICATIONS OF BNI iB Hasanah in PT BNI SYARIAH BANDA ACEH CITY BRANCH (Survey of Customer Behavior Against Banda Aceh) - Hasna Lathifah; Israk Ahmadsyah; Cut Dian Fitri (LPPM Universitas Malikussaleh, 2019)
This reserch aims to give recomendation to BNI Syariah about the reason of the choice of products. The effect of cultural, social, personal, and psychologies to customers behavior. The data collections are obtained from 50 respondens. The reserch utilizes mix anlyzing by using mix method triangular approach and multiple linear regression. The result showed that culture does mot give siqnificant effect, but social, personal and psycology are positive and siqnificanly influence the cusmer behavior. The effectivity of the cognitive aspect was concluded less effective, but affective and conative aspects showed it's that both are effective. The recommendation given to BNI Syariah is to communicate things related to cognitive aspect roomates and maximize social, personal, and physycological variables.